Determination of Polymorphism Location of the Calcareous Corpuscles in the Tapeworm Bothriocephalus acheilognathi - Al-Kallak, S. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research includes the histochemical study of the cestode, Bothriocephalus acheilognathi in order to determine location and concentration of the polymorphism of the calcareous corpuscles in different tissues and organs of the above mentioned cestode. In general, it was noticed abundance polymorphism in calcareous corpuscles, which appeared in the shape of spread clusters, oval structures and floats in location in biological units such as longitudinal muscles, mesenchymal tissue and reproductive organs. The present research indicated various polymorphisms in calcareous corpuscles. Furthermore, the polymorphism in calcareous corpuscles indicates their importance as they ensure survival and continuation of the parasite in its host.